Examining the factors influencing Malaysian parents' intention toward human papillomavirus (HPV) vaccination for children - Noor Amira Syazwani, Abd Rahman; Jamal Rizal, Razali; Mohd Rozaimy, Ridzuan; Ju, Soon Yew (Human Resource Management Academic Research Society (HRMARS), 2022)
Vaccination is one of the most successful public health strategies for disease prevention and control. In Malaysia, the National Immunization Programme (NIP) was established in the 1950s, and among the vaccines available to students are the Human Papillomavirus (HPV) vaccines. Many developed countries have worked actively to promote immunization among children. Similarly, in Malaysia, such vaccination programs were started a long time ago. However, the number of vaccine rejection cases recorded at government clinics has increased from time to time. Hence, this study examines the factors influencing Malaysian parents' intention to vaccinate their children. The theory of Planned Behaviour (TPB) was employed to underpin the study, and two additional predictors were adopted to enhance the overall regression model. The study found that except for perceived behavioral control (PCB), all independent variables (i.e., attitude, subjective norms, the role of anticipated regret, and trust in health authorities) have significantly influenced parents' intentions to vaccinate their children. It is hoped that this study will be able to supplement the existing information on vaccination in Malaysia and help the government formulate suitable vaccination programs. Nevertheless, the study only analyses the Malaysian parents’ intention toward the HPV vaccination. Therefore, future research is needed to study other vaccines available. A longitudinal study might be conducted to establish the cause-effect relationships empirically.